"It's always hard being a mom, but the pandemic has made everything harder": A qualitative exploration of the experiences of perinatal women during the COVID-19 pandemic. (June 2022) - Kinser, P.; Jallo, N.; Moyer, S.; Weinstock, M.; Barrett, D.; Mughal, N.; Stevens, L.; Rider, A.
Abstract: Background: Understanding the psychosocial impacts of the COVID-19 pandemic in vulnerable groups, such as pregnant and parenting women, is a critical research and clinical imperative. Although many survey-based perinatal health studies have contributed important information about mental health, few have given full voice about the experiences of pregnant and postpartum women during the prolonged worldwide pandemic using a qualitative approach. Objective: The purpose of this study is to explore the lived experience of pregnant and postpartum women in the United States during the ongoing COVID-19 pandemic. Design: Qualitative phenomenological study. Setting: This study was conducted in the community, by recruiting women throughout the U.S. Participants: Fifty-four pregnant and postpartum women participated in qualitative interviews. Methods: Data from one-on-one semi-structured interviews were analyzed using a team-based phenomenological qualitative approach. Results: Two key themes were apparent: the pandemic has shined a light on the many typical struggles of motherhood; and, there is a lack of consistent, community-based or healthcare system resources available to address the complex needs of pregnant and postpartum women, both in general and during the pandemic. Conclusions: Going forward, as the world continues to deal with the current pandemic and possible future global health crises, health care systems and providers are encouraged to consider the suggestions provided by these participants: talk early and often to women about mental health; help pregnant and postpartum women create and institute a personal plan for early support of their mental health needs and create an easily accessible mental health network; conceptualize practice methods that enhance coping and resilience; practice in community-based and interdisciplinary teams (e.g., midwives, doulas, perinatal social workers/ psychotherapists) to ensure continuity of care and to foster relationships between providers and pregnant/ postpartum women; and consider learning from other countries' successful perinatal healthcare practices. Registration: Number (& date of first recruitment): not applicable. Tweetable abstract: Pregnant and postpartum women insist that mental health care must be overhauled, stating the pandemic has highlighted inherent cracks in the system.